Comparative study of cases with and without C5 palsy after cervical spine surgery - Fukuzawa, Kosuke; Uehara, Masashi; Ikegami, Shota; Miyaoka, Yoshinari; Oba, Hiroki; Hatakenaka, Terue; Kurogochi, Daisuke; Fukuzawa, Takuma; Sasao, Shinji; Shigenobu, Keisuke; Mimura, Tetsuhiko; Takahashi, Jun (Interdisciplinary neurosurgery : Advanced techniques and case management, 2025)
•This comparative investigation sought to clarify the incidence and risk factors of C5 palsy in patients receiving cervical spine surgery.•C5 palsy occurred in 13.2% of patients undergoing cervical spine surgery.•C5 palsy showed significant associations with male gender, AAS, and surgical range including C4-5. C5 palsy is a known complication after cervical spine surgery, although incidence rates range widely from 0 to 30% in the literature. The causes of C5 palsy also remain unknown, with many studies describing contradictory risk factors. This comparative investigation sought to clarify the incidence and risk factors of C5 palsy in patients receiving cervical spine surgery. The medical data of 433 consecutive patients (305 male and 128 female; mean age: 67.7 years) who underwent their first cervical spine surgery were retrospectively examined. The cohort was divided into the C5 palsy group and the non-C5 palsy group, and associated factors were examined by multivariate analysis. Postoperative C5 palsy was observed in 57 of 433 (13.2 %) patients. Atlantoaxial subluxation (AAS) was significantly more common in the C5 palsy group (10.5 %) than in the non-C5 palsy group (3.7 %) (p = 0.035). Regarding procedural details, surgical range including C4-5 was significantly more common in the C5 palsy group (80.7 % vs. 63.8 %, p = 0.015). Multivariate analysis revealed significant associations with C5 palsy for male gender (p = 0.025), AAS (p < 0.001), and surgical range including C4-5 (p = 0.002). C5 palsy occurred in 13.2% of patients undergoing cervical spine surgery. Significant associations with male gender, AAS, and surgical range including C4-5 suggest the need for additional perioperative considerations in such patients.